Linguocultural Approach to The Study Of Youth Slang - Talibjanova Aziza Lutfullaevna (Genius Journals, 2021)
The article studies the lexical composition of youth slang, systematizes the linguistic characteristics of this subsystem of the language, reveals structural and functional features that reflect the specifics of the worldview of its speakers and are fully manifested in the language of modern journalism, focused on a youth audience.
Keywords: Linguistic And Cultural Studies; Linguistic Worldview; Youth Slang; World Perception